2011
DOI: 10.4021/jem54w
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Melatonin Administration Effectively Deprograms the Negative Influence of Neonatal Hypothyroidism on Immature Follicles but not on Mature Follicles and Body and Ovarian Weights

Abstract: Background: The impact of simultaneous melatonin administration on neonatal progmming by hypothyroidism (HPOT + MT) on adult ovarian functions and serum hormone profiles has been evaluated in the Charles foster strain of rats. Methods:The female neonates were rendered hypothyroid (HPOT) by feeding lactating mothers with 6-propyl 2-thiouracil (PTU) through drinking water and were simultaneously administered with melatonin (MT) (40 µg/animal/day) from day 0 to day 21 in the evening at 16:30 hours just prior to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Thyroid hormones (TH) play essential roles in regulation of energy expenditure, as well as in regulation of growth and maturation of many organs and systems, including brain, skeleton, and reproductive organs (Mann et al, 2006;Thakkar et al, 2011). Secretions of TSH and thyroid hormones are of circadian nature (Weeke and Gundersen, 1978;Jordan et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid hormones (TH) play essential roles in regulation of energy expenditure, as well as in regulation of growth and maturation of many organs and systems, including brain, skeleton, and reproductive organs (Mann et al, 2006;Thakkar et al, 2011). Secretions of TSH and thyroid hormones are of circadian nature (Weeke and Gundersen, 1978;Jordan et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Thakkara et al [9] observed that, simultaneous melatonin administration effectively deprogramed the negative influence of neonatal hypothyroidism on immature follicles but not on mature follicles and body and ovarian weights. This different finding may be attributed to the different organ (ovary) they worked on.…”
Section: Discussionmentioning
confidence: 99%
“…The most common disorders of the thyroid gland are hyperthyroidism and hypothyroidism [1] . Hyperthyroidism is a condition in which the thyroid gland secretes too much thyroid hormone and hypothyroidism results in insufficient amounts of thyroid hormone [9] . Both hyperthyroidism and hypothyroidism have been linked to cell damage [10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T4 is the dominant hormone released from the thyroid gland, while T3 is biologically more active and originates mainly from peripheral deiodination of T4 [5]. Thyroid hormones play essential role in regulation of metabolic rate, regulation of growth, maturation of many organs and systems, including brain, skeleton, reproductive organs and energy expenditure [24,37].…”
Section: Introductionmentioning
confidence: 99%